New Perspectives on Corporate Social Responsibility: Locating the Missing Link - O'Riordan, Linda (Springer, 2015)
Providing a timely contribution to the ongoing questions surrounding topics which are by definition subject to varying stakeholder interpretations, this book addresses “the missing link” between theoretical CSR concepts and everyday management practice. It acts as a guide to awaken managers to the advantages of adopting a CSR “mindset” when developing sustainable business strategies. The book consists of three parts: 1) A theoretical realm which establishes the key concepts and rationale for the adoption of a sustainable CSR approach, 2) A practical realm which addresses putting CSR and sustainability into business practice, 3) An educational realm which proposes how to incorporate the concepts into teaching and training.